KESIAPAN GURU MI MUHAMMADIYAH TAMBAKSARI BLORA TERHADAP IMPLEMENTASI KURIKULUM MERDEKA BELAJAR - Munawar, Mohammad (Sekolah Tinggi Agama Islam Muhammadiyah Blora, 2023)
This research took place at MI Muhammadiyah Tambaksari Blora. This research is a qualitative descriptive research. Grade 1 and grade 4 teachers of MI Muhammadiyah numbered one person each as a source of research data through interviews. What indicators must be met by a teacher in order to successfully implement this independent learning curriculum? What are the implications of teacher readiness in MI Muhammadiyah Tambaksari Blora on the implementation of the independent learning curriculum? The readiness of MI Muhammadiyah Tambaksari Blora teachers in implementing an independent curriculum can be said to be ready in theory, however, in practice it still needs to be deepened through independent training. The level of readiness shown can be a consideration for schools to immediately respond to problems. In addition, the concept of an independent curriculum needs to be understood by all elements of educational institutions, so that in its application it can run optimally, effectively and efficiently and be able to achieve the goals of the independent curriculum itself. Careful readiness is needed by teachers, so that they can implement curriculum implementation in accordance with the objectives. Independent training is needed by a teacher with limited time training, so that all problems / difficulties about the implementation of the independent curriculum are resolved.Keywords: Readiness, Freedom to Learn